Penyelarasan Fatwa Dan Kaedah Penyelesaiannya Di Malaysia: Suatu Kajian Literatur - Muhamad Miziazam, Yahya; Mansor, Sulaiman; Hasan, Ahmad (Universiti Malaysia Pahang, 2018)
This article highlights the issue of the lack of fatwa coordination between the Council of Fatwa of the National Council for Islamic Religious Affairs Malaysia (JFK) and the State Fatwa Committees in Malaysia. The purpose of this paper is to focus on the issue of fatwa coordination in Malaysia. It is an issue that is often debated by academics at the university level. Various theories and approaches have been proposed and formulated to address the differences in fatwa, especially between states and the federal government. Thus, this literature highlights the opinions and views of researchers who have raised this problem in their study. Variables such as enactment barriers in states, local customes, different educational backgrounds among the muftis and weaknesses of guidelines provided by JAKIM are the factors that lead to such problems. Hence, data collection method used was based on the content analysis especially previous academic studies conducted on the issue of fatwa coordination in Malaysia. Finally, findings of these studies shows discrepancies which needs further studies on the issue.